Detailed Study on the Effect of Pharmaceutical Excipients on the Release Kinetics of Bilayer Tablet - Bibaswan Mishra; Satyajit Panda (Current Aspects in Pharmaceutical Research and Development Vol. 3, 2021)
In the present work, the main objective was to develop bilayer extended release matrix tablets of etoricoxib by providing a loading dose followed by maintenance dose that expected to improve the therapeutic efficacy of the medication with less toxic effect. As most bilayer tablets are developed as part of a Life Cycle Management Program, the bilayer technology provides a possibility of prolonging patent life of a drug product. Bilayer tablets of etoricoxib was developed successfully with the meticulous proportion of release controlling Hydroxy propyl methyl cellulose K100 (HPMC K100) and lactose. The tablets were prepared by wet granulation technique. Granules for immediate layer and extended layer for different formulations were prepared separately. The formulations were developed and evaluations were performed to examine the parameters that affect the in vitro performance of the tablets. The drug-excipient compatibility was ensured by Fourier transform infrared spectroscopy (FTIR) study. The values of physical parameters of all formulations were found within appreciable limit. Formulation containing HPMC K 100 and lactose in the proportion of 2:1 in the extended release layer was able to release 26.22% of drug in 15 min and shown a steady release of drug for an extended period of 12 h. The dissolution data was put in Korsemeyer–Peppas model in order to find out n value, which describes the drug release mechanism. The n-value of different formulations were found to be variable. The Fourier transform infrared spectroscopy (FTIR) study revealed absence of any other new peaks and also no differences in the positions of the absorption bands in the bilayer tablet F8 that indicate the lack of significant interactions between etoricoxib and other excipients. It had been concluded that once daily immediate-and extended release bilayer tablet of etoricoxib can be formulated with profound physical characteristics and dissolution properties. This resulted in reducing the daily dose and thus minimise the cardiovascular toxicity of etoricoxib.